Excitonic fractional quantum Hall hierarchy in Moiré heterostructures - Kwan, YH; Hu, Y; Simon, SH; Parameswaran, SA (American Physical Society, 2022)
We consider fractional quantum Hall states in systems where two flat Chern number C=±1 bands are labeled by an approximately conserved 'valley' index and interchanged by time reversal symmetry. At filling factor ν = 1 this setting admits an unusual hierarchy of correlated phases of excitons, neutral particle-hole pair excitations of a fully valley-polarized 'orbital ferromagnet’ parent state where all electrons occupy a single valley. Excitons experience an effective magnetic field due to the Chern numbers of the underlying bands. This obstructs their condensation in favor of a variety of crystalline orders and gapped and gapless liquid states. All these have the same quantized charge Hall response and are electrically incompressible, but differ in their edge structure, orbital magnetization, and hence valley and thermal responses. We explore the relevance of this scenario for moir'e heterostructures of bilayer graphene on a hexagonal boron nitride substrate.